Single tube liquid biopsy for advanced non‐small cell lung cancer. Issue 12 (28th January 2019) - de Wit, Sanne; Rossi, Elisabetta; Weber, Sabrina; Tamminga, Menno; Manicone, Mariangela; Swennenhuis, Joost F.; Groothuis‐Oudshoorn, Catharina G.M.; Vidotto, Riccardo; Facchinetti, Antonella; Zeune, Leonie L.; Schuuring, Ed; Zamarchi, Rita; et al.
Abstract : The need for a liquid biopsy in non‐small cell lung cancer (NSCLC) patients is rapidly increasing. We studied the relation between overall survival (OS) and the presence of four cancer biomarkers from a single blood draw in advanced NSCLC patients: EpCAM high circulating tumor cells (CTC), EpCAM low CTC, tumor‐derived extracellular vesicles (tdEV) and cell‐free circulating tumor DNA (ctDNA). EpCAM high CTC were detected with CellSearch, tdEV in the CellSearch images and EpCAM low CTC with filtration after CellSearch. ctDNA was isolated from plasma and mutations present in the primary tumor were tracked with deep sequencing methods. In 97 patients, 21% had ≥2 EpCAM high CTC, 15% had ≥2 EpCAM low CTC, 27% had ≥18 tdEV and 19% had ctDNA with ≥10% mutant allele frequency. Either one of these four biomarkers could be detected in 45% of the patients and all biomarkers were present in 2%. In 11 out of 16 patients (69%) mutations were detected in the ctDNA. Two or more unfavorable biomarkers were associated with poor OS. The presence of EpCAM high CTC and elevated levels of tdEV and ctDNA was associated with a poor OS; however, the presence of EpCAM low CTC was not. This single tube approach enables simultaneous analysis of multiple biomarkers to explore their potential as a liquid biopsy. Abstract : What's new? Liquid biopsies may provide a convenient and patient‐friendly approach to inform prognosis and prediction of the best treatment management. Here, the authors studied the relation between overall survival and the presence of four different cancer biomarkers from a single blood draw in 97 advanced non‐small cell lung cancer (NSCLC) patients. The presence of EpCAM high‐expressing circulating tumour cells and elevated levels of tumour vesicles and tumour DNA were associated with a poor clinical outcome, but not the presence of EpCAM low‐expressing CTC. This single tube approach enables simultaneous analysis of several biomarkers to explore their potential as a liquid biopsy.